KOMUNIKASI PERSUASIF ORANG TUA DALAM MEMBIASAKAN IBADAH SHALAT ANAK DI JORONG LIMO KAMPUANG - Rhada Oktaviani; Tomi Hendra (KOLONI, 2022)
Communication is very important for humans to interact with each other. Communication is also needed by parents to educate and guide children. In educating and guiding children parents use good words and language so that it is easy for the child's mind to understand. In getting used to worshiping children's prayers, of course, persuasive communication is needed from parents for guidance, direction, and invitation. The background of this research is because there are still children who leave the prayer services in Jorong Limo Kampuang. And the purpose of this research is to find out parents' persuasive communication and parents' persuasive communication barriers in getting children used to praying. The type of research that the author uses is field research with a descriptive qualitative approach. As well as the research location is in Jorong Limo Kampuang, the research informants are parents who have children aged 7-12 years and the researchers used a purposive sampling technique in which the sample was selected based on certain considerations. To obtain information, the data collection used is observation, interviews and documentation. The results of the research are Persuasive Communication of Parents in Getting Accustomed to Prayer Worship for Children in Jorong Limo Kampuang, which consists of, first: Persuasive communication of parents that instills discipline, where parents get used to worship pray for children by inviting them well, and educating children with the teachings explained by the teacher studying them. second: Parents who provide understanding, where in getting used to praying, parents guide and direct children. third: parents who liberate and follow the child's will, where in getting used to worshiping children's prayers parents do not force children to perform prayer services. fourth: parents who are apathetic, where in getting used to worshiping children's prayers, parents do not really care when children do not pray. Barriers to parents' persuasive communication in getting used to praying for children there are two inhibiting factors, first: internal factors, lazy, tired and tired, mental condition is still unstable, it's hard to get up early. Second: external factors, parents' lack of time for children, environment (playing with friends), technology (mobile phones, television). Keywords: persuasive communication, parents and children, prayer.